Hydrography-Driven Variability of Optically Active Constituents of Water in the South Brazilian Bight: Biogeochemical Implications - Gonçalves-Araujo, Rafael; Röttgers, Rüdiger; Haraguchi, Lumi; Brandini, Frederico Pereira (Frontiers in Marine Science, 2019)
The South Brazilian Bight (SBB) is a hydrographically dynamic environment with strong seasonality that sustains a diverse planktonic community involved in diverse biogeochemical processes. The inherent optical properties (IOPs; e.g., absorption and scattering coefficients) of optically actives constituents of water (OACs; phytoplankton, non-algal particles–NAP, and colored dissolved organic matter–CDOM) have been widely employed to retrieve information on biogeochemical parameters in the water. In this study conducted in the SBB, a cross-shelf transect was performed for biogeochemistry and hydrographic sampling during a summer expedition. Our research aimed to determine the distribution and amount of the optically active constituents of water based on their spectral signature, in relation to the distribution of water masses in the region. That allows us to get insights into the biogeochemical processes within each water mass and in the boundaries between them. We observed a strong intrusion of South Atlantic Central Water (SACW) over the shelf, mainly driven by the wind action. With that, phytoplankton development was fueled by the input of nutrients, and increased chlorophyll-a (Chl-a) concentrations were observed within the shallowest stations. Colored dissolved organic matter (CDOM) did not follow the distribution of dissolved organic carbon (DOC). Both CDOM and DOC presented high values at the low salinity Coastal Water (CW), as an indication of the continental influence over the shelf. However, CDOM was inversely correlated with salinity and lowest values were observed within Tropical Water (TW), whereas DOC values within TW were as high as within CW, indicating an autochthonous DOM source. Additionally, a deep Chl-a maximum (DCM) was noticed in the boundary between the TW and SACW. Along with the DCM, we observed the production of fresh, non-colored DOM attributed to the microbial community. Finally, our results suggest that CDOM is photodegraded at the surface of CW. This is mainly due to the Ekman transport effect over the region that traps CW at the surface, making it longer exposed to solar radiation.